2017
DOI: 10.9775/kvfd.2017.17667
|View full text |Cite
|
Sign up to set email alerts
|

Doğu Anadolu-Türkiye Koşullarında Farklı Bal Arısı (Apis mellifera L.) Genotiplerinin Kışlama Yeteneği ve Koloni Performanslarının Karşılaştırılması

Abstract: Citation of This ArticleCengiz MM, Erdoğan Y: Comparison of wintering ability and colony performances of different honeybee (Apis mellifera L.) genotypes in Eastern Anatolian/Turkey conditions. Kafkas Univ Vet Fak Derg, 23 (6): 865-870, 2017. DOI: 10.9775/kvfd.2017 AbstractIn this study, wintering ability and some physiological properties of Buckfast, Carniolan, Caucasian and Erzurum honeybee genotypes were investigated in Eastern Anatolian conditions. During the wintering season of 2014, a total of 48 coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The average honey yield in the control group was 18.50±1.57 kg/colony. The honey production of Caucasian honey bees was found to be lower than the findings by Genç et al (1999), andYeninar et al (2009) (reported as 30.6 and 36.3 kg/colony, respectively), but they were consistent with the previous results reported by Kutluca (2003), Cengiz and Erdoğan (2017) (informed as 18.13 and 19.28 kg/colony, respectively). In addition, it has been reported that supplementary feeding increased the total honey yield in previous studies (Karacaoğlu et al 2003;Dodoloğlu et al 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average honey yield in the control group was 18.50±1.57 kg/colony. The honey production of Caucasian honey bees was found to be lower than the findings by Genç et al (1999), andYeninar et al (2009) (reported as 30.6 and 36.3 kg/colony, respectively), but they were consistent with the previous results reported by Kutluca (2003), Cengiz and Erdoğan (2017) (informed as 18.13 and 19.28 kg/colony, respectively). In addition, it has been reported that supplementary feeding increased the total honey yield in previous studies (Karacaoğlu et al 2003;Dodoloğlu et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…The obtained values were used as a measure of adult bee development (Akyol et al, 2014). The brood area was measured by PUCHTA method (S = 3.14xA/2xa/2) in cm at 21 days intervals from April to October (Yücel & Kösoğlu, 2011;Akyol et al, 2014;Cengiz & Erdoğan, 2017). The obtained values were used as a measurement of the development of the brood area.…”
Section: Taking Data From Experimental Coloniesmentioning
confidence: 99%
“…The number of frames covered with bees was counted at 30-day intervals until September 5, when the honey harvest was made. The values obtained were recorded as the development of adult bees of the experimental groups (Cengiz and Erdoğan 2017).…”
Section: Number Of Frames Covered With Beesmentioning
confidence: 99%
“…Turkey, which has 7 different geographical regions with its own unique climate and vegetation, is an important country for honey production. Our country also contains 75% of the honey plant species identified in the world [1,2] .…”
Section: Introductionmentioning
confidence: 99%